PLN Waqf Solarfunding: Waqf-Based Solar Panel Innovation as a Form of Development in Papua to Create a Halal Philanthropic Industry - Rizky Ulul Azmy; Indarisuci; Pipit Amanda (Jurnal Multidisiplin Madani, 2023)
The background of this research and innovative writing is the problem of inequality and equitable development which is still lacking in the Papua region, Indonesia. The lack of equitable distribution of development in the Papua region causes income inequality compared to other regions. Cash waqf is one of the instruments of Islamic philanthropy that can be a solution to overcome these two problems. The existence of cash waqf specifically for the development of electricity resources in the Papua region is expected to facilitate the Papuan people in their economic activities so that people's income will increase and encourage good economic growth in the Papua region. This innovative research uses descriptive qualitative methods which make descriptions, systematic, factual and accurate descriptions of facts, characteristics and relationships between phenomena that exist in the field studied. The data is analyzed to find the right solution to dealing with the problem. The results of the research show that with the benefits of cash waqf for the development of electricity resources in the Papua region, it will be the right solution to encourage equitable distribution of development in Indonesia while reducing the problem of inequality. The proposed innovations are not only adapted to the community environment so that they are environmentally friendly but are also supported by advanced technology so that they can be implemented more easily and more efficiently to be accessed by the community. So that people can make waqf through crowdfunding waqf in the PLN-mobile application. By working together through PLN and BWI it is hoped that the development of electricity resources in the Papua region will be more effective and efficient. In addition, it is hoped that the Papuan people will be involved during the innovation program, starting from the development process to monitoring so that it can become an evaluation for the parties involved